القواعد الأصولية المتعلقة بدلالات الألفاظ من خلال الموطأ: باب المعاملات نموذجا (Preliminary Principles Concerning the Connotations of Words in al-Mu’atta’: The Chapter on Transactions as a Specimen) - الهنداوي, حسن إبراهيم; بوصوف, فارس (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص تهدف هذه الدراسة إلى إبراز بعض القواعد الأصولية المتعلقة بدلالات الألفاظ؛ التي بواسطتها يتمكن العلماء من استنباط الأحكام الفقهية العملية من أدلتها التفصيلية، بتسليط الضوء على باب المعاملات من خلال موطأ الإمام مالك، كما سعت لإثبات تلك القواعد الأصولية، وتحليلها، ومحاولة تفعيلها بما يُأهل العقل الفقهي في التعامل السليم في فهم النصوص الشرعية، وذلك من خلال اتباع المنهج الاستقرائي في تتبع النصوص، والأدلة من خلال ما ورد في باب المعاملات، وتتبع أقوال فقهاء وأصوليي المذهب المالكي في هذه المسائل التي يراها الباحث أنها تخدم واقع الناس. وتتجلى أهم نتائج هذا البحث في: أن إبراز هذه القواعد يضفي تنوعا وثراء على الساحة العلمية في صناعة الاجتهاد، والمساهمة في استيعاب ما يستجد من مسائل تقتضيها المجتمعات الإسلامية المعاصرة. الكلمات المفتاحية: القواعد الأصولية، دلالات الألفاظ، باب المعاملات، الموطأ. Abstract This study aims to highlight some of the preliminary principles concerning the connotations of words. Through these principles, scholars can derive legal rulings from its particular evidences and shed light on the transaction chapter of Imam Malik's Mu’atta’. The study also strives to establish these principles, analyze them, and apply them in order to enhance the legal-mind to understand the legal texts better. This is done by the means of inductive method which tracks down the legal texts, the evidences stated in the transaction chapter and those legal statements of the Maliki fiqh and uÎËl scholars which the researcher found relevant for the people. The most important result of this research is that these highlighted principles extend the diversity and versatility of the scientific arena when it comes to the ijtihÉd work. The principles contribute to accommodate the emerging issues necessary for the contemporary Muslim society. Key words: Preliminary Principles, Connotations of Words, the Chapter on Transactions, al-Mu’atta’